Pencegahan Jentik pada Fase Akuatik dan 4M Plus di SDN Pematang Panjang - Pardi Affandi Affandi (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2026)
Dengue Hemorrhagic Fever (DHF) is an endemic disease in Indonesia caused by the dengue virus and transmitted by Aedes aegypti mosquitoes. One effective measure to prevent its transmission is the eradication of mosquito larvae during the aquatic phase. This article discusses an outreach program conducted at SDN Pematang Panjang, Banjar Regency, which aimed to enhance elementary school students’ understanding of the dangers of DHF and the importance of clean and healthy living behaviors through the 4M Plus movement. The method employed was interactive counseling using psychological, scientific, and practical approaches, accompanied by evaluations through pretests and posttests. The results showed an improvement in students’ comprehension of DHF prevention, as indicated by increased posttest scores and enthusiasm throughout the activity. Early education of this kind is expected to serve as a long-term strategy to reduce DHF cases in endemic areas.